Ohmic contacts on n-type and p-type cubic silicon carbide (3C-SiC) grown on silicon. (April 2019) - Spera, M.; Greco, G.; Lo Nigro, R.; Bongiorno, C.; Giannazzo, F.; Zielinski, M.; La Via, F.; Roccaforte, F.
Abstract: This paper is a report on Ohmic contacts on n-type and p-type type cubic silicon carbide (3C-SiC) layers grown on silicon substrates. In particular, the morphological, electrical and structural properties of annealed Ni and Ti/Al/Ni contacts has been studied employing several characterization techniques. Ni films annealed at 950 °C form Ohmic contacts on moderately n-type doped 3C-SiC (ND 1 × 10 17 cm −3 ), with a specific contact resistance of 3.7 × 10 −3 Ω cm 2 . The main phase formed upon annealing in this contact was nickel silicide (Ni2 Si), with randomly dispersed carbon in the reacted layer. In the case of a p-type 3C-SiC with a high doping level (NA 5 × 10 19 cm −3 ), Ti/Al/Ni contacts were preferable to Ni ones, as they gave much lower values of the specific contact resistance (1.8 × 10 −5 Ω cm 2 ). Here, an Al3 Ni2 layer was formed in the uppermost part of the contact, while TiC was detected at the interface. For this system, a temperature dependent electrical characterization allowed to establish that the thermionic field emission rules the current transport at the interface. All these results can be useful for the further development of a device technology based on the 3C-SiC polytype.